Emotional stability, performance orientation, job performance on east java firms Indonesia - Karuniawati Hasanah (Cita Konsultindo Research Center, 2024)
this study is to see the effect of the role of performance orientation in mediating the influence between emotional stability on job performance. This study used primary data from the distribution of questionnaires to manufacturing companies in East Java, Indonesia totaling 139 questionnaires. Data analysis using smartPLS 3. The results of this study show that full mediation orientation performance on the influence between emotional stability on job performance. Individual performance orientation is used as one of the factors of self-motivation to be able to achieve maximum performance. Each individual has a different performance orientation, judging from the goals to be achieved. The results of this study are expected to contribute to the role of managers in organizations to consider aspects of performance orientation should be formed from the beginning of the career of the employee.